Evaluation of rotated constellation in DVB-T2 based on measurement data - Suwansukho, Nattapan; Promwong, Sathaporn (My University, 2019)
This paper describes the result of using Rotated Constellation Feature that include Digital Terrestrial Television second generation network in Thailand. The measured results were carried out from 20 measured location, located in Bangkok, Thailand.
Keywords: Bit Error Rate; Error Vector Magnitude; Modulation Error Ratio; Noise Margin; OFDM; Rotated Constellation